Remote learning in the time of Covid-19: an interactive learning calculus II for engineers (Mat235) by using microsoft teams digital platform / Aslina Omar and Samsiah Abdul Razak - Omar, Aslina; Abdul Razak, Samsiah
While schools and many higher education institutions have been forced to shut down around the globe due to pandemic Covid-19, the demand for digital transformation in education has reached new heights. Many educators are struggling to move classes online as quickly and painlessly as possible. Universiti Teknologi MARA (UiTM) is also no exception and had to transform their learning and teaching process from face-to-face courses to Open and Distance Learning (ODL) mode. To overcome the potential effects of the pandemic, UiTM has been looking for ways to provide access to education by using ODL. Open and Distance Learning (ODL) is a general term for the use of telecommunication to provide or enhance learning. Using ODL, it makes about quality e-learning and e- content more accessible to both facilitators and learners. Various online teaching platforms can be used in implementing ODL, but the lecturers need to consider the Internet speed of their students. ODL activities conducted are a blend of asynchronous (without real-time interaction) and synchronous (real-time interaction) online learning. There are various ODL platforms for teaching and learning activities such as Google Meet, Google Classroom, WebEx, and Zoom. The key idea in this paper is to use the Microsoft Teams platform in order to implement ODL in teaching Calculus II for Engineers (MAT 235). By using Microsoft Teams, the lecturers can set up a team for the class, with different lectures and class dates assigned to different channels. Each channel would have a series of tabs that would, in effect, constitute the class. There would be no textbook. Instead, real-time digital inking and problem solving with in-class chat streams and collaboration from the learning community would serve as the course material. As a result, everything in the educational experience works together, and they can make sure all the students have the best learning experience because Microsoft Teams can offer a lot of benefits for both students and lecturers.